Levonorgestrel intrauterine system: Current role in management of heavy menstrual bleeding - Navneet Magon; Monica Chauhan; Poonam Goel; Sonia Malik; Krishan Kapur; Alka Kriplani; Lakhbir Dhaliwal; Suchitra N Pandit (Wolters Kluwer Medknow Publications, 2013)
A review of literature was conducted to report on the effectiveness of levonorgestrel intrauterine system (LNG-IUS) in women with heavy menstrual bleeding (HMB). The relevant data were obtained by computerized searches of PubMed up to December 2012 and other references available with the authors. Information was obtained from references listed. Studies and case reports were excluded if they did not specifically provide information about LNG-IUS usage in women with HMB. After perusal, each relevant publication was summarized and appraised in terms of whether it contained information relevant to the stated objective. Available data shows that LNG-IUS therapy is effective and safe, providing significant reduction of menstrual bleeding in patients with HMB. LNG-IUS is a good strategy to reduce the number of hysterectomies in women with HMB.